Sternberg's diagnostic surgical pathology. - Sternberg, Stephen S.; Mills, Stacey E.; Carter, Darryl (Wolters Kluwer Lippincott Williams & Wilkins, 2010)
A two-volume reference that presents the most advanced diagnostic techniques and information on all known disease entities. It features more than 90 preeminent surgical pathologists who offer expert advice on the diagnostic evaluation of every type of specimen from every anatomic site. It contains over 4,400 full-color photographs.